Improving Students’ Speaking Ability through Communicative Activities Using Songs at SMA Yasmor Oenoni - Armi Reinnati; Lailatul Musyarofah; Kani Sulam Taufik (Budapest International Research and Critics University, 2022)
The study’s goal was to find out the improvements of the students’ speaking by using songs at SMA Yasmor Plus Oenoni in the academic year of 2021/2022. The issue was that they were less motivated to improve their speaking skills. This study was classified as action research. This study included 17 students of the class XI IPA and an English teacher as a research collaborator. Interviews, observations, and documentation were the instruments used. In this study, the researchers used both qualitative and quantitative data to analyze the data. The research findings revealed that using songs as a teaching media in speaking activities in the English class was proven to be effective in increasing students’ motivation to speak. It has the potential to draw students’ attention and increase their motivation. They were also given opportunities to practice their public speaking skills. This was also evident from the speaking scores showed that the number of students in the category of excellent at the first meeting was only three, they were able to increase their category to 17 which indicated that they significantly improved in some aspects of their speaking ability, such as pronunciation, grammar, and vocabulary.